Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Connect with professionals on our platform to receive accurate answers to your questions quickly and efficiently. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Hello,
[tex]3 x^{2} -y^{3} -y^{3}-z \\ =3 x^{2} -2y^{3}-z \\ \\ Replacing:\,\, \,\,x=3\,\, \,\,y=-2\,\, \,\,z=-5 \\ \\ =3(3)^{2} -2(-2)^{3}-(-5) \\ =3*9-2*(-8)+5 \\ =27+16+5 \\ =48[/tex]
Answer: 48
[tex]3 x^{2} -y^{3} -y^{3}-z \\ =3 x^{2} -2y^{3}-z \\ \\ Replacing:\,\, \,\,x=3\,\, \,\,y=-2\,\, \,\,z=-5 \\ \\ =3(3)^{2} -2(-2)^{3}-(-5) \\ =3*9-2*(-8)+5 \\ =27+16+5 \\ =48[/tex]
Answer: 48
Answer:
The value of [tex]3x^2-y^3-y^3-z[/tex] is, 48
Step-by-step explanation:
Given the equation:
Let f(x, y, z) = [tex]3x^2-y^3-y^3-z[/tex] .....[1]
Like terms states that the terms which have the same variables.
Combine like terms in equation [1];
[tex]f(x, y, z) =3x^2-2y^3-z[/tex] ......[2]
Given: x= 3 , y= -2 and z = -5.
Substitute these given values in [2] we get;
[tex]f(3, -2, -5) =3(3)^2-2(-2)^3-(-5)[/tex]
[tex]f(3, -2, -5) =3(9)-2(-8)-(-5)[/tex] = 27 + 16 +5 = 48.
Therefore, the value of [tex]3x^2-y^3-y^3-z[/tex] is, 48
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.